(10 - k) · k = 0
1 способ.
10 - k = 0 и k = 0
k = 10 - 0
k = 10
2 способ.
10k - k² = 0
Домножим обе части уравнения на (-1)
k² - 10k = 0
D = b² - 4ac = (-10)² - 4 · 1 · 0 = 100 - 0 = 100
√D = √100 = 10
х₁ = (10-10)/(2·1) = 0/2 = 0
х₂ = (10+10)/(2·1) = 20/2 = 10
Ответ: х₁ = 0; х₂ = 10.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
(10 - k) · k = 0
1 способ.
10 - k = 0 и k = 0
k = 10 - 0
k = 10
2 способ.
10k - k² = 0
Домножим обе части уравнения на (-1)
k² - 10k = 0
D = b² - 4ac = (-10)² - 4 · 1 · 0 = 100 - 0 = 100
√D = √100 = 10
х₁ = (10-10)/(2·1) = 0/2 = 0
х₂ = (10+10)/(2·1) = 20/2 = 10
Ответ: х₁ = 0; х₂ = 10.